2010
DOI: 10.1007/s12177-011-9065-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical inhibition of fatty acid synthase: molecular docking analysis and biochemical validation in ocular cancer cells

Abstract: anti-cancer therapeutics. The ocular cancer, retinoblastoma cells were treated with fatty acid synthase (FASN) enzyme inhibitors: cerulenin, triclosan and orlistat. The IC 50 and dose-dependent sensitivity of cancer cells to FASN inhibitors decrease in biologic enzyme activity, and cell morphology alterations were analysed. Molecular interactions of enzyme-inhibitor complexes were studied by molecular modelling and docking simulations. The crystal structures of ketoacyl synthase (PDB ID:3HHD) (cerulenin) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…Henry and Fair’s results were based on only one day of exposure, whereas Liu et al observed reduced viability and a decreasing IC 50 in MCF-7 cells across four days [23,26]. This decrease in IC 50 has also been observed in the studies examining retinoblastoma cells over 96 hours [27,28,29]. Furthermore, Henry and Fair reported slight cytotoxic responses beginning at ~20 μg/mL, within the range observed by both Liu et al and Deepa et al (2012) [26,27].…”
Section: Resultsmentioning
confidence: 81%
“…Henry and Fair’s results were based on only one day of exposure, whereas Liu et al observed reduced viability and a decreasing IC 50 in MCF-7 cells across four days [23,26]. This decrease in IC 50 has also been observed in the studies examining retinoblastoma cells over 96 hours [27,28,29]. Furthermore, Henry and Fair reported slight cytotoxic responses beginning at ~20 μg/mL, within the range observed by both Liu et al and Deepa et al (2012) [26,27].…”
Section: Resultsmentioning
confidence: 81%
“…However, in our structure, the hER TCL binding site is located away from the active site at the protein-pro- (38). The TCL binding energy in our allosteric site is estimated to be approximately Ϫ12 kcal/mol, indicating that the allosteric binding site might be more energetically favorable.…”
mentioning
confidence: 80%
“…TCL Inhibition Mode-TCL inhibition of FAS was initially believed to act as a traditional active site inhibitor, similar to bacterial ER (38). However, in our structure, the hER TCL binding site is located away from the active site at the protein-pro- (38).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Semi-flexible docking was done in which protein was kept as rigid and the ligands as flexible [35]. For all the ligands, the possible torsion angles were set to rotate freely.…”
Section: Methodsmentioning
confidence: 99%